KONJUNGSI BAHASA INGGRIS DAN BAHASA BANGGAI (SUATU ANALISIS KONTRASTIF) - LIMAYAS, MERLIN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This research entitled â€œConjunction in English and Banggai Language (A Contrastive Analysis)â€Â  is an attempt to contrast conjunction in both languages in terms ofÂ  form, function, and meaning in order to find out the similarities and differences between English and Banggai language. The problems of this research are what are the forms, functions, and meanings of conjunctions in English and Banggai language and to find out the similarities and differences between them. The purpose of this study is to identify, classify, and describe the forms, functions, and meanings ofÂ  conjunctions in English and Banggai language and to analyze the differences and similarities of conjunctions in these two languages. The method of this study is descriptive method. Theories that used areÂ  Aarts and Aarts (1982), John and Yates (1982), and Lado (1972). Investigation has been done through the library and field research. The English data has been collected from some English grammatical books, linguistic books, and from internet whereas the Banggai data has been collected from the native informant speakers and the Bible written in Banggai language. The result shows that English and Banggai language have similarities and differences in forms and functions. In terms of form there is complex conjunction in English whereas in the Banggai language this case just found one conjunction based on the data obtained. In terms of functionÂ  English and Banggai has two main functions : coordinating conjunctions that connect word, phrase, clause and sentences are equivalent and subordinating conjunctions to link clauses and sentences are not equivalent, as well as the Banggai language also has that functions. In terms of meaningÂ  both English and Banggai language have similarities. Keywords : Conjunction, English, Banggai language, form, function, meaning.